Going back to the roots: the fourth generation of Swedish eco-villages. (2nd October 2018) - Magnusson, Dick
ABSTRACT: Local reactions to climate change and sustainable development take various forms. The literature on grassroots innovation has grown recently, and it illustrates the myriad of initiatives that are actively working with the issues. The eco-village movement is one example of a grassroots innovation that reacts and adapts to its prerequisites, all striving for an alternative living with reduced environmental impact. This paper focuses on the development of eco-villages in Sweden, arguing that in recent years a fourth generation of initiatives has emerged, with ideals close to the pioneers of the first generation's idealistic views and ambitions for alternative living as a way of reacting to global trends. The fourth generation is highly diverse in form and goals, but with an emphasis on outreach and networking as well as more focus on small-scale agriculture and permaculture. This paper presents, through literature reviews, database searches and interviews, how the eco-village idea has moved between initiatives and has taken various forms over the generations. In the first generation via books, reports and personal contacts, in the second and third also via contractors and professionals, and in the fourth via the internet and social media in order to attract members and have impact.